Chemical plating solution and quartz optical fiber metallization treatment method
By improving the electroless plating solution formulation and simplifying the pretreatment steps, the adhesion and consistency problems during nickel-phosphorus alloy plating on the surface of quartz fiber are solved, high-quality plating and efficient production are achieved, and environmental impact is reduced.
Patent Information
- Application Number
- CN202411718390.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art When plating nickel-phosphorus alloys on the surface of quartz optical fibers, coarse treatment is required to improve the adhesion of the coating, but this will lead to a decrease in the fiber strength and the electroless plating solution is easy to decompose, resulting in discontinuity of the coating and affecting batch consistency.
The improved electroless plating solution formulation, including nickel sulfate, sodium hypophosphite, propionic acid, boric acid, citric acid, lactic acid, surfactant and stabilizer, is used to improve the stability and reusability of the plating solution by optimizing the mass ratio and pH of these components, and to eliminate the heating sensitization and activation steps in the pretreatment.
Without reducing the fiber strength, the bonding force between the substrate and the metal layer is improved, and high-quality electroless nickel-plated phosphorus alloy on the surface of quartz fiber is achieved, reducing environmental pollution and resource waste, and improving production efficiency and coating quality.
Smart Images

Figure CN119551914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical fiber surface treatment technology, and more specifically, relates to a chemical plating solution and a quartz optical fiber metallization treatment method. Background Art
[0002] Chemical plating is a method that does not require an external power source and uses an appropriate chemical reducing agent to reduce metal ions in the chemical plating solution to metal and deposit it on the surface of the substrate. Among the many chemical plating processes, chemical nickel-phosphorus alloy plating is widely used due to its superior performance. The nickel-phosphorus alloy coating not only has high hardness, high wear resistance and high corrosion resistance, but also has good weldability. In addition, the phosphorus content of the coating can be adjusted and the thickness of the coating is evenly distributed, which makes it an ideal choice in many industrial applications.
[0003] Quartz optical fiber has been widely used in optical communication, optical sensing and other fields due to its high light transmittance and low loss. Quartz optical fiber can be processed into tapered / wedge-shaped lens optical fiber to improve the coupling efficiency with waveguide devices, or made into optical fiber sensor to measure the stress and strain of objects, but the premise of these applications is to firmly fix the optical fiber at a certain distance and angle, which puts higher requirements on the surface treatment of the optical fiber. Metallizing the surface of quartz optical fiber and fixing it by welding is one of the effective methods to achieve precise positioning of optical fiber.
[0004] The traditional chemical plating solution for nickel-phosphorus alloy plating of quartz optical fiber requires the quartz optical fiber to be pre-treated including a roughening process. This is because the bare optical fiber has an extremely small diameter and an extremely smooth surface, making it extremely challenging to implement chemical nickel plating on its surface. Usually, the optical fiber surface needs to be roughened before chemical plating to increase the adhesion of the coating. In order to improve the bonding strength between the matrix and the metal layer, hydrofluoric acid and fluorosilicic acid are used to roughen the quartz optical fiber. This treatment method causes a significant decrease in the strength of the optical fiber. It is necessary to solve the problem of how to improve the bonding strength between the matrix and the metal layer without reducing the strength of the optical fiber.
[0005] Although roughening treatment can improve the adhesion of the coating, it often leads to a decrease in the toughness of the optical fiber, increases the risk of optical fiber breakage, and may have an adverse effect on the optical transmission performance of the optical fiber. Therefore, a non-roughening optical fiber surface chemical plating process has been developed, such as the optical fiber surface chemical nickel-phosphorus plating process provided by Chinese patent document CN1827848A and the optical fiber surface chemical nickel-phosphorus plating process provided by Chinese patent document CN111020539A.
[0006] The metal Ni-P coating layer on the optical fiber surface prepared by the chemical nickel-phosphorus plating process without roughening of the optical fiber surface is evenly distributed, the coating quality is good, there is no roughening in the plating process, and there is no damage to the optical fiber removing the coating layer. However, under the premise of no roughening, in order to ensure the firmness of the coating, the chemical plating Ni-P layer process conditions are harsh. Before using the chemical plating Ni-P solution, the sensitizing solution and the activating solution need to be heated to sensitize and activate the optical fiber, and the optical fiber is subsequently placed in the chemical plating Ni-P solution to obtain a qualified optical fiber with a coating. In addition, the chemical plating solution is prone to decomposition during use, resulting in a situation where the metal coating is locally discontinuous when the nickel-phosphorus metal layer on the optical fiber surface is chemically plated in large quantities, and the coating quality fluctuates during mass production, and the batch consistency is poor. Re-adjusting the composition of the chemical plating solution not only increases the production cost, but also causes environmental pollution and waste of resources. Summary of the invention
[0007] In view of the above defects or improvement needs of the prior art, the present invention provides a chemical plating solution and a quartz optical fiber metallization treatment method. The chemical plating solution has high stability and is reusable. The chemical plating solution can achieve high-quality chemical plating of nickel-phosphorus alloy on the surface of the quartz optical fiber without damaging the mechanical properties and optical properties of the optical fiber, and can effectively improve the adhesion of the coating on the surface of the optical fiber, improve the efficiency of the use of the chemical plating solution, and reduce the impact on the environment. In the pretreatment of the optical fiber before using the chemical plating solution, the quartz optical fiber can be sensitized and activated without heating the sensitizing solution and the activating solution, thereby reducing the heating step of the sensitizing solution and the activating solution, making the pretreatment sensitization and activation process more convenient and efficient, and the quality of the coating obtained by subsequent chemical plating is high.
[0008] To achieve the above object, according to one aspect of the present invention, there is provided a chemical plating solution, characterized in that it comprises the following components in mass concentration:
[0009] Nickel sulfate: 15g / L-34g / L;
[0010] Sodium hypophosphite: 16g / L-28g / L;
[0011] Propionic acid: 16g / L-28mL / L;
[0012] Boric acid: 15g / L-25g / L;
[0013] Citric acid: 0g / L-8g / L;
[0014] Lactic acid: 0.35 g / L-5 mL / L;
[0015] Surfactant: 0.01g / L-0.08g / L;
[0016] Stabilizer: 0.0001g / L-0.001g / L;
[0017] Lead acetate: 0.0003g / L-0.001g / L;
[0018] The surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium n-octyl sulfate, and the stabilizer is thiourea and / or potassium iodate;
[0019] The pH value of the chemical plating solution is 4-4.6.
[0020] Preferably, the mass ratio of sodium hypophosphite to propionic acid is 1:1-1:1.5. With such a mass ratio, the stability of the plating solution and the utilization rate of sodium hypophosphite can be improved, so that the consistency of the plating layer is good.
[0021] Preferably, the mass ratio of nickel sulfate to boric acid is 0.9: 1-1.67: 1. With such a mass ratio, the plating speed of the chemical plating solution and the reusability of the chemical plating solution can be stabilized.
[0022] Preferably, the mass of sodium hypophosphite is m 1 , the sum of the masses of citric acid and lactic acid is m 2 , and m 1 :m 2 =2:1-4:1. Using such a mass ratio can improve the stability of the plating solution, avoid the decomposition of the plating solution, increase the utilization rate of sodium hypophosphite and nickel sulfate, and make the coating smooth and bright.
[0023] Preferably, the mass ratio of the surfactant to the stabilizer is 80:1-125:1. With such a mass ratio, the deposition rate of the nickel layer on the optical fiber surface, the pores, pits and cracks on the nickel layer surface can be controlled, the quality and performance of the plated nickel layer can be improved, and the solution can reduce evaporation to achieve a clean, clear and sustainable state.
[0024] Preferably, the mass concentration of sodium dodecyl sulfate is 0-0.08 g / L, the mass concentration of sodium dodecylbenzene sulfonate is 0-0.06 g / L, and the mass concentration of sodium n-octyl sulfate is 0-0.02 g / L. Such concentrations can better allow the gas in the plating solution to escape, reduce the porosity of the coating, make the coating continuity good and the bonding strength excellent, and can also reduce the sour taste, reduce the evaporation of the solution and play a role in heat preservation.
[0025] Preferably, the mass concentration of thiourea is 0-0.001 g / L, and the mass concentration of potassium iodate is 0-0.005 g / L. With such concentrations, the plating solution can be guaranteed not to spontaneously decompose at a higher plating speed, the plating process can be carried out stably and orderly, and the reusability of the plating solution can be improved.
[0026] According to another aspect of the present invention, a method for metallizing a quartz optical fiber is provided, characterized in that the method comprises the following steps:
[0027] 1) Pre-treating the quartz optical fiber, wherein the pre-treatment includes the steps of removing the coating layer, cleaning, degreasing, baking, sensitizing, washing, activating and baking in sequence; wherein the sensitizing solution used for sensitization and the activating solution used for activation are both at room temperature, i.e., no heating is required;
[0028] 2) placing the pretreated quartz optical fiber into the chemical plating solution to plate a nickel-phosphorus alloy;
[0029] 3) taking out the quartz optical fiber plated with the nickel-phosphorus alloy from the chemical plating solution and rinsing it;
[0030] 4) Place the quartz optical fiber plated with nickel-phosphorus alloy in an oven for drying.
[0031] Preferably, in step 1), in the sensitizing solution, SnCl 2 The mass concentration of is 30g / L~40g / L, and the volume concentration of HCl is 50mL / L~60mL / L;
[0032] In the activation solution, PdCl 2 The mass concentration of is 1g / L~2g / L, and the volume concentration of HCl is 10mL / L~20mL / L.
[0033] Preferably, in step 2), the initial temperature of the chemical plating solution is 75°C, and the temperature is increased from 75°C to 90°C at a rate of 0.5°C / min, and then maintained at 90°C for 60 min to 85 min.
[0034] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0035] 1) The chemical plating solution of the present invention uses one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium n-octyl sulfate as a surfactant. The surfactant has wettability. When the quartz optical fiber is plated with a nickel-phosphorus alloy layer in the chemical plating solution, the surface tension of the coating can be significantly reduced, which helps the gas in the plating solution to escape, reduces the porosity of the coating, and makes the coating have good continuity and excellent bonding strength. In addition, the surfactant also acts as a foaming agent, and forms a layer of foam on the surface of the coating, which can keep warm, reduce the evaporation loss of the chemical plating solution, reduce the sour taste, and make the dirt sandwiched in the foam and not enter the coating and the chemical plating solution, so that the coating and the chemical plating solution can be kept clean. The dirt in the coating and the chemical plating solution can be easily cleaned by cleaning the foam.
[0036] In addition, the amount of surfactant used also affects the size and smoothness of the coating particles. The present invention selects the appropriate type and mass concentration of surfactant in the chemical plating solution to make the nickel-phosphorus alloy coating on the surface of the quartz optical fiber smooth and continuous with basically no protruding large particles.
[0037] 2) The chemical plating solution of the present invention can sensitize and activate the quartz optical fiber without heating the sensitizing solution and the activating solution during the optical fiber pretreatment, thereby reducing the heating step of the sensitizing solution and the activating solution, making the pretreatment sensitization and activation process more convenient and efficient, and the quality of the coating obtained by the subsequent chemical plating is high.
[0038] 3) The chemical plating solution of the present invention has good stability, is not prone to decomposition, and can be reused. This is because the stabilizer can inhibit the spontaneous decomposition of the chemical plating solution, so that the plating process can proceed in an orderly manner under control; the stabilizer can be preferentially adsorbed on the surface of the particles to inhibit the catalytic reaction, thereby masking the catalytic active center and preventing the nucleation reaction on the surface of the particles, but does not affect the normal chemical plating process on the surface of the quartz optical fiber.
[0039] In addition, complexing agents such as citric acid and / or lactic acid in the electroless nickel plating solution can control the free Ni 2+ In addition to reducing the concentration, it can also inhibit the deposition of nickel phosphite in the solution, improve the stability of the chemical plating solution, and extend the life of the chemical plating solution.
[0040] 4) In the chemical plating solution of the present invention, the stabilizer is selected from the type of complexing agent such as thiourea and / or potassium iodate and the ratio between the stabilizer and the main salt (nickel sulfate) is controlled to affect the comprehensive quality of the coating, so that the nickel-phosphorus alloy coating plated on the surface of the quartz optical fiber can be deposited evenly and well.
[0041] 5) The chemical plating solution of the present invention uses boric acid and propionic acid as buffers in the chemical nickel plating solution, so that the solution has a buffering capacity, that is, the pH value of the solution does not change too much during the plating process and can be maintained within a certain range, and the chemical plating solution can be reused.
[0042] When used repeatedly, there will be no missing plating on the surface of the quartz optical fiber, and there is no need to add special supplementary solution to the chemical plating solution. It is also guaranteed that the coating is uniform and there will be no missing plating each time it is used.
[0043] 6) The chemical plating solution of the present invention can control the free Ni available for reaction by reasonably adjusting the ratio of the mass of sodium hypophosphite to the sum of the mass of citric acid and lactic acid, the mass ratio of sodium hypophosphite to propionic acid, and the mass ratio of nickel sulfate to boric acid. 2+ Concentration can improve the stability of chemical plating solution, prolong the life of chemical plating solution, and has good coating adhesion, excellent coating quality and environmentally friendly characteristics.
[0044] 7) The quartz optical fiber metallization treatment method of the present invention eliminates the roughening step required in the traditional coating process, simplifies the pretreatment process, significantly reduces the process complexity and time cost, and improves the production efficiency. Even without roughening, the coating of the quartz optical fiber still maintains good bonding strength, ensuring the close adhesion of the coating to the optical fiber surface, avoiding problems such as cracking, peeling or flaking, and improving the bonding strength between the quartz optical fiber matrix and the nickel-phosphorus alloy coating without roughening or reducing the strength of the optical fiber.
[0045] 8) The quartz optical fiber metallization treatment method of the present invention significantly improves the efficiency of chemically plating nickel-phosphorus alloy on the optical fiber surface through an optimized plating process and a reusable chemical plating solution, shortens the production cycle, and improves production efficiency.
[0046] 9) The quartz optical fiber metallization treatment method of the present invention requires simple equipment, reduces equipment investment costs, and is suitable for the production needs of small and medium-sized enterprises.
[0047] In summary, the present invention achieves the purpose of optimizing the pretreatment process of quartz optical fiber, not reducing the strength of optical fiber, reducing the risk of decomposition of chemical plating solution, and realizing the reuse of chemical plating solution through the improved chemical plating solution formula, and simplifies the pretreatment process, improves production efficiency and coating quality. The present invention significantly improves the efficiency and stability of chemical plating of nickel-phosphorus alloy on the surface of quartz optical fiber, improves the utilization rate of chemical plating solution, and reduces environmental pollution, which is of great significance for promoting the further application of optical fiber in the fields of optical communication and optical sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1a is a surface morphology of the quartz optical fiber treated with the chemical plating solution of Example 1 under an optical microscope;
[0049] Figure 1b This is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 1 after tearing test under an optical microscope;
[0050] Figure 1c This is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 1 after thermal shock testing under an optical microscope;
[0051] Figure 2a is a surface morphology of the quartz optical fiber treated with the chemical plating solution of Example 2 under an optical microscope;
[0052] Figure 2b This is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 2 after tearing test under an optical microscope;
[0053] Figure 2cThis is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 2 after thermal shock testing under an optical microscope;
[0054] Figure 3a is a surface morphology of the quartz optical fiber treated with the chemical plating solution of Example 3 under an optical microscope;
[0055] Figure 3b This is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 3 after tearing test under an optical microscope;
[0056] Figure 3c This is a surface morphology image of the quartz optical fiber treated with the chemical plating solution of Example 3 after thermal shock testing under an optical microscope;
[0057] Figure 4a , Figure 4b Surface morphology of different parts of a quartz optical fiber treated with a chemical plating solution of a comparative example under an optical microscope;
[0058] Figure 5a , Figure 5b The surface morphology of different parts of the surface coating of the quartz optical fiber treated with a chemical plating solution in a comparative example after a tear test under an optical microscope is shown. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0060] The process of chemically plating nickel-phosphorus alloy layer on the surface of non-roughened optical fiber usually requires a long sensitization and activation step to ensure the formation of a continuous and uniform coating. Moreover, the sensitization and activation steps are very sensitive to the process temperature. The traditional process of chemically plating nickel-phosphorus alloy layer on the surface of non-roughened optical fiber cannot obtain a uniform and continuous coating below 12°C. The continuity of the coating is better at 25°C to 35°C. The molecular movement is violent above 45°C, which is not conducive to the formation of a continuous and uniform coating, and local discontinuity occurs. Therefore, two strategies are currently used to ensure the effect of sensitization and activation, so that the catalytically active palladium ions are uniformly attached to the surface of the optical fiber glass part: First, extend the reaction time, usually the sensitization and activation reaction time is more than 10 minutes, generally 15 minutes; second, strictly control the sensitization and activation temperature, for example, strictly control the sensitization temperature at 25°C and the activation temperature at 35°C; these two strategies are sometimes used at the same time.
[0061] However, the strategy of strictly controlling the sensitization and activation temperature has greatly restricted large-scale industrial production. It is difficult to strictly control the reaction temperature in industrial plants, which is not conducive to mass industrial manufacturing of coated optical fibers. On the one hand, extending the sensitization and activation time reduces production efficiency. On the other hand, the adhesion effect of palladium ions is slightly poor if only the strategy of extending the sensitization and activation time is adopted. It is necessary to increase the reaction temperature to 80°C or even above 85°C in the chemical nickel plating process to improve the reaction efficiency and ensure the continuity of the coating. The existing chemical plating solution has poor high-temperature stability. In the chemical nickel plating process, if the reaction temperature is too high, it is easy to decompose, and the plating solution evaporates quickly. The chemical plating process is continuously carried out in large-scale production. The coating is locally unstable, discontinuous or rough on the surface, and the product batch consistency is poor.
[0062] In view of the above problems, the present invention aims to propose an improved method for nickel-phosphorus alloy plating of optical fiber, which improves the thermal stability of the chemical plating solution, reduces the risk of decomposition of the chemical plating solution, and reduces the process conditions for sensitization and activation by improving the chemical plating solution formula. A short-term sensitization and activation treatment is performed without strictly controlling the ambient temperature, and the reaction activity is improved in combination with a high-temperature chemical plating process to obtain an optical fiber with a continuous and smooth nickel-phosphorus metal coating, good coating quality, and high product strength. The time of the overall process flow is shortened, the requirements for the control of the ambient temperature are reduced, and the production efficiency is improved.
[0063] At the same time, due to the excellent thermal stability of the chemical plating solution provided by the present invention, when nickel-phosphorus metal-coated optical fibers are continuously produced in large quantities, the composition of the chemical plating solution is stable and can even be reused. The nickel-phosphorus metal coating on the surface of the produced optical fibers is of reliable quality and has good product consistency.
[0064] Specifically, the formulas of samples #1 to #9 of the chemical plating solution of the present invention are shown in Table 1.
[0065] Table 1 Chemical plating solution formula
[0066]
[0067] In addition: The temperatures of the chemical plating solution samples 1# to 9# when chemically plating quartz optical fiber are 70°C, 65°C, 80°C, 75°C, 60°C, 65°C, 65°C, 70°C, and 85°C respectively.
[0068] The advantages of the chemical plating solution of the present invention are analyzed below in combination with three typical embodiments and a comparative example.
[0069] Example 1
[0070] Choose a silica optical fiber with a diameter of 125 μm and a length of 1 meter.
[0071] The chemical plating solution formula is as follows:
[0072] Nickel sulfate (NiSO 4 6H 2 O): 24g / L;
[0073] Sodium hypophosphite (NaH 2 PO 2 ·H 2 O): 18g / L;
[0074] Propionic acid (C 3 H 6 O 2 ): 18mL / L;
[0075] Boric acid (H 3 BO 3 ): 20g / L;
[0076] Citric acid (C 6 H 8 O 7 ): 4g / L;
[0077] Lactic acid (C 3 H 6 O 3 ): 3mL / L;
[0078] Surfactant: 0.01 g / L; the surfactant used is sodium n-octyl sulfate.
[0079] Stabilizer: 0.0001g / L; the stabilizer is potassium iodate.
[0080] Lead acetate: 0.0003 g / L;
[0081] pH value of chemical plating solution: 4.2.
[0082] The preparation method of the above chemical plating solution is as follows:
[0083] 1) Place nickel sulfate, sodium hypophosphite, propionic acid, boric acid, citric acid, lactic acid, surfactant, stabilizer and lead acetate in a beaker, add pure water and stir until completely dissolved.
[0084] 2) Use ammonia water to adjust the pH to 4.2 and ensure the solution is uniform.
[0085] An activation solution was added to the chemical plating solution to conduct a stability test. After 8 hours, no decomposition of the chemical plating solution occurred.
[0086] The metallization treatment method of quartz optical fiber is as follows:
[0087] 1) Pre-treating the quartz optical fiber, including the following sub-steps:
[0088] 1.1) Use a thermal stripper to remove the coating layer on the surface of the quartz optical fiber at a fixed length; use a dust-free cloth dipped in anhydrous ethanol to gently wipe the bare fiber to ensure that the surface residue is removed; place the optical fiber in an ultrasonic cleaner and use deionized water to clean it for 1 minute to remove dirt on the surface of the optical fiber.
[0089] 1.2) Prepare a NaOH solution with a concentration of 30 g / L and soak the bare fiber for 10 minutes at room temperature. Then, place the fiber in an ultrasonic cleaner and clean it with deionized water for 2 minutes to ensure that the NaOH is fully removed.
[0090] 1.3) Soak the bare fiber in a solution containing 30g / L SnCl 2 and 50mL / L HCl (37%) sensitizing solution for 5 minutes.
[0091] 1.4) Soak the bare fiber in a solution containing 1g / L PdCl 2 The optical fiber was immersed in an activation solution of 10 mL / L HCl (37%) for 5 minutes. The optical fiber was rinsed with deionized water for 30 seconds, and then placed in an oven at 120°C for 10 minutes.
[0092] The sensitizing solution used in the sensitization of step 1.3) and the activation solution used in the activation of step 1.4) are both at room temperature, that is, no heating or strict temperature control is required, the same below. Note: In the chemical system, the design temperature of room temperature is -20 to 200°C.
[0093] 2) The pretreated quartz optical fiber is immersed in the prepared chemical plating solution. The chemical plating solution is heated from 75°C to 90°C at a rate of 0.5°C / min, and then maintained at 90°C for 50 minutes.
[0094] 3) After the reaction is completed, the quartz optical fiber is taken out from the chemical plating solution and rinsed with deionized water to remove the unreacted chemicals.
[0095] 4) Place the quartz optical fiber plated with nickel-phosphorus alloy in an oven, set the temperature to 120°C, and bake for 10 minutes to dry.
[0096] Reference Figure 1a , using a microscope to observe the coating, no cracking, peeling or flaking was found, the coating continuity was good, no discontinuity. Figure 1b After being torn off 6 times with 3M 600 test tape and then subjected to ultrasonic treatment for 5 minutes (frequency 120Hz), the nickel-phosphorus alloy coating was observed under a microscope. No cracking or peeling was found, and the coating was intact. Figure 1cAfter the optical fiber was thermally shocked (baked at 250℃ for 1h and quickly placed in an ice-water mixture at 0℃), the coating was observed under a microscope and no cracking, peeling or flaking was found. The coating had good continuity and no discontinuity. The nickel-phosphorus alloy coating had high quality. The chemical plating solution was recovered and the experiment was repeated. The optical fiber coating quality test results were good.
[0097] Example 2
[0098] Choose a silica optical fiber with a diameter of 125 μm and a length of 0.5 m.
[0099] The chemical plating solution formula is as follows:
[0100] Nickel sulfate (NiSO 4 6H 2 O): 30g / L;
[0101] Sodium hypophosphite (NaH 2 PO 2 ·H 2 O): 20g / L;
[0102] Propionic acid (C 3 H 6 O 2 ): 20mL / L;
[0103] Boric acid (H 3 BO 3 ): 25g / L;
[0104] Citric acid (C 6 H 8 O 7 ): 6g / L;
[0105] Lactic acid (C 3 H 6 O 3 ): 2mL / L;
[0106] Surfactant: 0.022 g / L; the surfactant is sodium dodecyl sulfate;
[0107] Stabilizer: 0.0002g / L; thiourea is used as stabilizer;
[0108] Lead acetate: 0.0005 mg / L;
[0109] pH: 4.5.
[0110] An activation solution was added to the chemical plating solution to conduct a stability test. After 8 hours, no decomposition of the chemical plating solution occurred.
[0111] The preparation method of the above chemical plating solution is as follows:
[0112] 1) Place nickel sulfate, sodium hypophosphite, propionic acid, boric acid, citric acid, lactic acid, surfactant, stabilizer and lead acetate in a beaker, add pure water and stir until completely dissolved.
[0113] 2) Use ammonia water to adjust the pH to 4.5 and ensure a uniform solution.
[0114] The metallization treatment method of quartz optical fiber is as follows:
[0115] 1) Pre-treating the quartz optical fiber, including the following sub-steps:
[0116] 1.1) Use a thermal stripper to remove the coating layer on the surface of the quartz optical fiber at a fixed length; use a dust-free cloth dipped in anhydrous ethanol to gently wipe the bare fiber to ensure that the surface residue is removed; place the optical fiber in an ultrasonic cleaner and use deionized water to clean it for 1 minute to remove dirt on the surface of the optical fiber.
[0117] 1.2) Prepare a NaOH solution with a concentration of 50 g / L and soak the bare fiber for 30 minutes at room temperature. Then, place the fiber in an ultrasonic cleaner and clean it with deionized water for 2 minutes to ensure that the NaOH is fully removed.
[0118] 1.3) Soak the bare fiber in a solution containing 40g / L SnCl 2 and 60mL / L HCl (37%) sensitizing solution for 5 minutes.
[0119] 1.4) Soak the bare fiber in a solution containing 2g / L PdCl 2 The fiber was immersed in an activation solution of 20 mL / L HCl (37%) for 5 min. The fiber was rinsed with deionized water for 30 s, and then placed in an oven at 120°C for 10 min.
[0120] The sensitizing solution used in the sensitization of step 1.3) and the activation solution used in the activation of step 1.4) are both at room temperature, that is, no heating is required. Note: In the chemical system, the design temperature of room temperature is between -20 and 200°C.
[0121] 2) Immerse the pretreated quartz optical fiber in the prepared chemical plating solution, starting from 75°C, raising the temperature to 90°C at a rate of 0.5°C / min, and then maintaining the temperature at 90°C for 70 minutes.
[0122] 3) After the reaction is completed, the optical fiber is taken out from the chemical plating solution and rinsed with deionized water to remove unreacted chemicals.
[0123] 4) Place the quartz optical fiber plated with nickel-phosphorus alloy in an oven, set the temperature to 120°C, and bake for 10 minutes to dry.
[0124] Reference Figure 2a, using a microscope to observe the nickel-phosphorus alloy coating, the nickel-phosphorus alloy coating on the optical fiber surface has excellent quality and bonding strength. Figure 2b , after being torn off 6 times with 3M 600 test tape and then subjected to ultrasound for 5 minutes (frequency 120Hz), the coating was observed under a microscope. The coating was intact and had excellent bonding strength. Figure 2c After the optical fiber was thermally shocked (baked at 250℃ for 1h and quickly placed in an ice-water mixture at 0℃), the coating was observed under a microscope and no cracking, peeling or flaking was found. The coating had good continuity and no discontinuity. The chemical plating solution was recovered and the experiment was repeated. The optical fiber coating quality test results were good.
[0125] Example 3
[0126] Choose a silica optical fiber with a diameter of 125 microns and a length of 0.7 meters.
[0127] The chemical plating solution is the chemical plating solution used in Example 2, and the pretreatment is the solution used to pretreat the quartz optical fiber in steps 1.1) to 1.4) of Example 2. No supplementary solution is added to the chemical plating solution and the pretreatment process.
[0128] The metallization treatment method of quartz optical fiber is as follows:
[0129] 1) Pre-treating the quartz optical fiber, including the following sub-steps:
[0130] 1.1) Use a thermal stripper to remove the coating layer on the surface of the quartz optical fiber at a fixed length; use a dust-free cloth dipped in anhydrous ethanol to gently wipe the bare fiber to ensure that the surface residue is removed; place the optical fiber in an ultrasonic cleaner and use deionized water to clean it for 1 minute to remove dirt on the surface of the optical fiber.
[0131] 1.2) Prepare a NaOH solution with a concentration of 50 g / L and soak the bare fiber for 15 minutes at room temperature. Then, place the fiber in an ultrasonic cleaner and clean it with deionized water for 2 minutes to ensure that the NaOH is fully removed.
[0132] 1.3) Soak the bare fiber in a solution containing 40g / L SnCl 2 and 60mL / L HCl (37%) sensitizing solution for 5 minutes.
[0133] 1.4) Soak the bare fiber in a solution containing 2g / L PdCl 2 The fiber was immersed in an activation solution of 20 mL / L HCl (37%) for 5 min. The fiber was rinsed with deionized water for 30 s, and then placed in an oven at 120°C for 10 min.
[0134] The sensitizing solution used in the sensitization of step 1.3) and the activation solution used in the activation of step 1.4) are both at room temperature, that is, no heating is required. Note: In the chemical system, the design temperature of room temperature is between -20 and 200°C.
[0135] 2) The pretreated quartz optical fiber was immersed in the chemical plating solution of Example 2, starting from 75° C., the temperature was raised to 90° C. at a rate of 0.5° C. / min, and then kept at 90° C. for 60 minutes.
[0136] Reference Figure 3a , the nickel-phosphorus alloy coating was observed under a microscope, and no cracking, peeling or flaking was found. The coating had good continuity, no discontinuity, and excellent bonding strength. Figure 3b , after 3M600 test tape was torn off 6 times, and then ultrasonicated for 5 minutes (frequency 120Hz), the coating was observed under a microscope, and the coating was intact and had excellent bonding strength. Figure 3c After the optical fiber was thermally shocked (baked at 250℃ for 1h and quickly placed in an ice-water mixture at 0℃), the coating was observed under a microscope and no cracking, peeling or flaking was found. The coating had good continuity and no discontinuity. The chemical plating solution was recovered and the experiment was repeated. The optical fiber coating quality test results were good.
[0137] Comparative Example
[0138] Choose a silica optical fiber with a diameter of 125 μm and a length of 0.5 m.
[0139] The chemical plating solution formula adopts the nickel plating solution formula in the document "Acid Chemical Nickel Plating Process for Optical Fiber" published in Hunan University Journal (Natural Science Journal), Vol. 38, No. 2, February 2011, as follows:
[0140] Nickel sulfate (NiSO 4 6H 2 O): 16.24 g / L;
[0141] Sodium hypophosphite (NaH 2 PO 2 ·H 2 O): 17.6 g / L;
[0142] Propionic acid (C 3 H 6 O 2 ): 20mL / L;
[0143] Boric acid (H 3 BO 3 ): 20g / L;
[0144] pH: 4.8;
[0145] The preparation method of the above chemical plating solution is as follows:
[0146] 1) Dissolve nickel sulfate, sodium hypophosphite, propionic acid and boric acid respectively in deionized water;
[0147] 2) Slowly mix the four solutions together and stir until evenly mixed. Use ammonia to adjust the pH to 4.8 to ensure a uniform solution.
[0148] The metallization treatment method of quartz optical fiber is as follows:
[0149] 1) Pre-treating the quartz optical fiber, including the following sub-steps:
[0150] 1.1) Use a thermal stripper to remove the coating layer on the surface of the quartz optical fiber at a fixed length; use a dust-free cloth dipped in anhydrous ethanol to gently wipe the bare fiber to ensure that the surface residue is removed; place the optical fiber in an ultrasonic cleaner and use deionized water to clean it for 1 minute to remove dirt on the surface of the optical fiber.
[0151] 1.2) Prepare a NaOH solution with a concentration of 50 g / L and soak the bare fiber for 30 minutes at room temperature. Then, place the fiber in an ultrasonic cleaner and clean it with deionized water for 2 minutes to ensure that the NaOH is fully removed.
[0152] 1.3) Soak the bare fiber in a solution containing 40g / L SnCl 2 and 60mL / L HCl (37%) sensitizing solution for 5 minutes.
[0153] 1.4) Soak the bare fiber in a solution containing 2g / L PdCl 2 The fiber was immersed in an activation solution of 20 mL / L HCl (37%) for 5 min. The fiber was rinsed with deionized water for 30 s, and then placed in an oven at 120°C for 10 min.
[0154] 2) The pretreated quartz optical fiber was immersed in the chemical plating solution of Example 2, starting from 75° C., the temperature was raised to 88° C. at a rate of 0.5° C. / min, and then kept at 88° C. for 70 minutes.
[0155] 3) After the reaction is completed, the optical fiber is taken out from the chemical plating solution and rinsed with deionized water to remove unreacted chemicals.
[0156] 4) Place the coated optical fiber in an oven, set the temperature to 120°C, and bake for 10 minutes to dry.
[0157] Reference Figure 4a , Figure 4b , using an optical microscope to observe the plating layer, the nickel layer surface is rough with many particles, some leakage, and poor bonding strength. Figure 5a , Figure 5bAfter the 3M 600 test tape was torn off once, the coating was observed under a microscope and large pieces fell off, exposing the fiber matrix.
[0158] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chemical plating solution, characterized in that The following components are included in mass concentration: Nickel sulfate: 15g / L-34g / L; Sodium hypophosphite: 16g / L-28g / L; Propionic acid: 16g / L-28mL / L; Boric acid: 15g / L-25g / L; Citric acid: 0g / L-8g / L; Lactic acid: 0.35 g / L-5 mL / L; Surfactant: 0.01g / L-0.08g / L; Stabilizer: 0.0001g / L-0.001g / L; Lead acetate: 0.0003g / L-0.001g / L; The surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium n-octyl sulfate, and the stabilizer is thiourea and / or potassium iodate; The pH value of the chemical plating solution is 4-4.
6.
2. The chemical plating solution according to claim 1, characterized in that The mass ratio of sodium hypophosphite to propionic acid is 1:1-1:1.
5.
3. The chemical plating solution according to claim 1, characterized in that: The mass ratio of nickel sulfate to boric acid is 0.9:1-1.67:
1.
4. The chemical plating solution according to claim 1, characterized in that: The mass of sodium hypophosphite is m1, the sum of the masses of citric acid and lactic acid is m2, and m1:m2=2:1-4:
1.
5. The chemical plating solution according to claim 1, characterized in that: The mass ratio of the surfactant to the stabilizer is 80:1-125:
1.
6. The chemical plating solution according to claim 1, characterized in that: The mass concentration of sodium dodecyl sulfate is 0-0.08 g / L, the mass concentration of sodium dodecylbenzene sulfonate is 0-0.06 g / L, and the mass concentration of sodium n-octyl sulfate is 0-0.02 g / L.
7. The chemical plating solution according to claim 1, characterized in that: The mass concentration of thiourea is 0-0.001 g / L, and the mass concentration of potassium iodate is 0-0.005 g / L.
8. A method for metallizing a quartz optical fiber, characterized in that: The following steps are involved: 1) Pre-treating the quartz optical fiber, the pre-treating comprising the steps of removing the coating layer, cleaning, degreasing, baking, sensitizing, washing, activating and baking in sequence; wherein the sensitizing solution used for sensitization and the activating solution used for activation are both at room temperature; 2) Plating the pretreated quartz optical fiber into the chemical plating solution of any one of claims 1 to 7 to plate a nickel-phosphorus alloy; 3) taking out the quartz optical fiber plated with the nickel-phosphorus alloy from the chemical plating solution and rinsing it; 4) Place the quartz optical fiber plated with nickel-phosphorus alloy in an oven for drying.
9. The method for metallizing a quartz optical fiber according to claim 8, characterized in that: In step 2), the initial temperature of the chemical plating solution is 75°C, and the temperature is raised from 75°C to 90°C at a rate of 0.5°C / min, and then maintained at 90°C for 60min to 85min.
10. The method for metallizing a quartz optical fiber according to claim 8, characterized in that: In the sensitizing solution, the mass concentration of SnCl2 is 30 g / L to 40 g / L, and the volume concentration of HCl is 50 mL / L to 60 mL / L; In the activation solution, the mass concentration of PdCl2 is 1 g / L to 2 g / L, and the volume concentration of HCl is 10 mL / L to 20 mL / L.
Citation Information
Patent Citations
Method for preparing optical fiber cladding optical filter based on Ni-P chemical plating method
CN111020539A
Process for coarsening-free chemical plating of nickel-phosphor alloy on optical fiber surface and chemical plating solution thereof
CN1827848A